Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1038/nm0296-175
|View full text |Cite
|
Sign up to set email alerts
|

The role of interleukin–15 in T–cell migration and activation in rheumatoid arthritis

Abstract: Interleukin 15 (IL-15) is a novel cytokine with interleukin-2-like activity. It is also a potent T-lymphocyte chemoattractant. Rheumatoid arthritis (RA) is a chronic inflammatory disease characterized by the presence of activated T lymphocytes, macrophages and synoviocytes in the synovial membrane. The mechanisms of T-cell activation in RA are currently unclear. We report the presence of high concentrations of IL-15 in rheumatoid arthritis (RA) synovial fluid and have demonstrated its expression in the synovia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
365
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 446 publications
(379 citation statements)
references
References 34 publications
11
365
2
Order By: Relevance
“…Taken together, these results indicate that CXCL16 could induce migration of CXCR6-positive T cells (which are activated, memory, and type 1 cytokine-producing T cells) from peripheral blood into synovial tissue. It is also possible that migrated CD4 and CD8 T cells are stimulated with IL-15, which is expressed in the RA synovium (36,37), and then express CXCR6. Consequently, CXCL16 could retain the CXCR6-positive CD4 and CD8 T cells in the synovial tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, these results indicate that CXCL16 could induce migration of CXCR6-positive T cells (which are activated, memory, and type 1 cytokine-producing T cells) from peripheral blood into synovial tissue. It is also possible that migrated CD4 and CD8 T cells are stimulated with IL-15, which is expressed in the RA synovium (36,37), and then express CXCR6. Consequently, CXCL16 could retain the CXCR6-positive CD4 and CD8 T cells in the synovial tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated the expression of IL-15 on synoviocytes and synovial endothelial cells in RA (36,37). Although a few peripheral blood T cells expressed CXCR6 ( Figure 3A), stimulation with 30 ng/ml of IL-15 for 8 days significantly increased CXCR6 expression in vitro (for CD4, mean Ϯ SEM 30.2 Ϯ 6.5%; for CD8, 16.9 Ϯ 1.4% [P Ͻ 0.05]; n ϭ 5) compared with expression without IL-15 stimulation (for CD4, 4.0 Ϯ 1.0%; for CD8, 7.1 Ϯ 2.0%; n ϭ 5); these findings are similar to those previously reported (38).…”
Section: Expression Of Cxcr6 By Cd4 and Cd8 T Cellsmentioning
confidence: 96%
“…To understand the underlying immunological mechanisms leading to Treg deficiency in SLE, we focused on the roles of IL-2 and IL-15, two cytokines known to be critically involved in the differentiation and expansion of both Teff and Treg [41][42][43]46]. It has recently been shown that production of functional Treg may occur in the thymus independent of IL-2, but the survival and expansion of peripheral Treg are greatly reduced in the absence of IL-2 [26].…”
Section: Discussionmentioning
confidence: 99%
“…The imbalanced IL-2 versus IFN-c production therefore also reflects the dysregulated Teff functions. IL-15 is a pleiotropic cytokine akin to IL-2 [41,42], which is produced by monocytic cells including DC [48,49] rather than T cells. IL-15 mediates its functions through the b-and c-chains of the IL-2 receptor together with a unique IL-15 a-chain, and is known to be involved in the regulation of normal differentiation and expansion of T cells including Treg [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation